José Ignacio López Soria: “Science and technology lose their way when they ignore social relevance as the basis of knowledge” - Vásquez Rodríguez, Rafael (2025)
José Ignacio López Soria is a philosopher and historian born in Spain in 1937. He arrived in Peru in 1957 as a Jesuit novice. His academic training covers classical humanities, literature, philosophy and history, with specializations in Latin American narrative, modern philosophy, philosophy of existence, history of Peruvian emancipation, Lukacsian thought, history of Peruvian engineering and philosophy of interculturality. Since 1966, he has been a university professor in Peru, mainly at the National University of Engineering (UNI), where he was rector between 1984 and 1989 and has directed the History Center of UNI. He has contributed more than 30 books and numerous articles in national and international journals. His most recent publication is “La Categoría de Cosificación en Lukács”. Currently, he continues to actively participate in intellectual debates related to the sociology of literature, Lukacsian Marxism, postmodern perspectives and the philosophy of interculturality, which have earned him the “Francisco Miró Quesada Cantuarias 2024” Philosophy Prize, awarded by the Peruvian Society of Philosophy.